Fiscal Administration Versus Fiscal Policy: An Investigation into the Determinants of the Real Tax Revenues from Consumption Tax in Egypt - Zahran, Nariman (AUC Knowledge Fountain, 2024)
This thesis highlights the importance of fiscal administration relative to fiscal policies. It presents a broad view of the developments in both fields and tests their effects on real revenues from consumption tax in Egypt from fiscal year 2002 till 2023. It initially explains the proxies used for fiscal administration: the size of the tax base and the collection lag. The major fiscal policy change in Egypt was shifting from sales tax to Value-Added Tax (VAT) during fiscal year 2016/17. The effects of fiscal administration and fiscal policy on real tax revenues will be assessed using the Autoregressive Distributed Lag (ARDL) model for 22 years.